1989
DOI: 10.1111/j.1365-2621.1989.tb07899.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Pigment and Lipid Stability in Holstein Steer Beef by Dietary Supplementation with Vitamin E

Abstract: Pigment and lipid oxidation was investigated in fresh ground sirloin from control and vitamin E-supplemented (370 I.U./head/day) Holstein steers. Alpha-tocopherol levels were higher (PcO.05) in muscle from supplemented animals than from controls. During 6 days storage at 4"C, metmyoglobin accumulation and lipid oxidation (TBA) were grcatcr (PcO.05) in beef from control versus supplemented animals. TBA value and % metmyoglobin were highly correlated in the control (r=0.91) and supplemented (r=0.72) groups. TBA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
1
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(161 citation statements)
references
References 25 publications
9
142
1
9
Order By: Relevance
“…Besides, it was possible that, in the conditions of the present study, the basal levels of vitamin E in the diets, without vitamin supplementation, were sufficient for its incorporation in LD muscles of the animals. According to Faustman et al (1989), muscle tocopherol concentrations >3 µg/g of tissue did not appear to yield any added benefit for reducing lipid oxidation rates in ground sirloin from Holstein steers. The total tocopherol concentration in the muscle of animals fed soybean was 3.09 µg/g of tissue in the present study.…”
Section: Tbars Vitamin E and Meat Colormentioning
confidence: 86%
“…Besides, it was possible that, in the conditions of the present study, the basal levels of vitamin E in the diets, without vitamin supplementation, were sufficient for its incorporation in LD muscles of the animals. According to Faustman et al (1989), muscle tocopherol concentrations >3 µg/g of tissue did not appear to yield any added benefit for reducing lipid oxidation rates in ground sirloin from Holstein steers. The total tocopherol concentration in the muscle of animals fed soybean was 3.09 µg/g of tissue in the present study.…”
Section: Tbars Vitamin E and Meat Colormentioning
confidence: 86%
“…Lipid oxidation in fresh meat could also be due to MMb-H 2 O 2 and in the cooked meat by Fe 3+ released by MMb. MMb formation and accumulation of lipid oxidation products are positively correlated [28]. Mb oxidation precedes the muscular lipid oxidation [77] and could play a catalyst role in the process of deterioration of flavour [98].…”
Section: Juicinessmentioning
confidence: 93%
“…Our result are in agreement with previous studies [32] [33] that observed an increase of α-tocopherol in the meat from animals reared at pasture with supplementation. High concentrations of vitamin E in muscle have been shown to increase the oxidative stability of beef [34], since vitamin E reduces lipid oxidation, improving meat quality characteristics such as colour, flavour, texture and nutritional value, as well as increasing shelf-life [35].…”
Section: Resultsmentioning
confidence: 99%